HIGHER GEOLOGICAL EDUCATION IN UKRAINE: TRENDS AND PROSPECTS - Mikhailov , V.; Vyzhva, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper deals with the principles of upgrading higher geological education in Ukraine via the trends and requirements for educational process in the world, and highlights the importance of specialist training for national economies (mineral-raw complexes). Consideration is given to the system of training geologists in higher educational institutions of Ukraine, to the reports on the admissions to universities over the last years, and to the employment prospects for geology graduates in Ukraine. It is stated that every year about 400 graduates from HEI top up labor market, with actual need for only 200 specialists. The paper proposes ways to enhance geological education, and skills and habits of geology graduates, and focuses on basic qualities necessary for graduates to have successful employment prospects in labor market. The latter are the following: marstery and competence in the major, self-determination and originality of thinking, knowledge of foreign languages and ITs etc. The authors suggest ways to upgrade educational process prioritizing the development of new educational standards, reduction of the auditorium share in the cirriculum, reinforcement of language courses, compiling manuals, eleborating remote teaching programmes and lecture courses in English, launching English taught projects for master degree seekers etc . The authors submit a draft of Qualifications Framework for bachelor degree in geolgy that incorporates latest institutionalized requirements and directives (the new Law on higher education, in particular), list suggested topical modules for different majors that are used in the Institute of geology at Taras Shevchenko national university of Kyiv, and emphasize the importance of research work for education.
Keywords: geological education; educational standards; bachelor; master; mineral-raw complex